Case Report: Endoscopic submucosal dissection revealed isolated gastric metastasis from primary bladder urothelial carcinoma: clinicopathological analysis and literature review - Xu, Famei; Li, Guihua; Qiu, Guihong; Yu, Hongbo; Yin, Qing; Xu, Fabao; Jian, Tianzi (Frontiers in Medicine, 2025)
A 73-year-old male was admitted to our department with complaints of upper abdominal distension, accompanied by dull pain and belching for more than 10 days. Gastroscopy revealed a broad-based raised lesion, approximately 1.0 cm in diameter, on the anterior wall of the gastric body, with a central star-shaped depression, erosion, and surrounding congestion. Endoscopic ultrasonography showed a lesion on the lower anterior wall of the gastric body involving the submucosal layer, with a subsequent biopsy indicating cancer. Notably, the patient had undergone cystectomy seven months earlier, with a pathological diagnosis of an invasive high-grade nested variant of urothelial carcinoma staging pT2N0Mx. An endoscopic submucosal dissection (ESD) was eventually conducted for diagnostic purposes. A gross examination of the specimen revealed a superficial elevated tumor measuring 1.2 × 1 × 0.3 cm, with a central depression, a grey-white cut surface, and firm texture. Microscopically, the tumor cells exhibited architectural and cytomorphological features resembling those of a bladder tumor. Immunohistochemical staining was positive for GATA-3, 34βE12, CK7 and negative for p63, which were consistent with those observed in bladder tumors. Based on the clinicopathological features and medical history, a diagnosis of gastric oligometastatic urothelial carcinoma was made. Following ESD, the patient received four cycles of gemcitabine chemotherapy and showed no sign of recurrence at the 41-month follow-up.